Ischemic Heart Disease and Chronic Obstructive Pulmonary Disease Hospitalizations in Japan Before and After the Introduction of a Heated Tobacco Product - van der Plas, Angela; Antunes, Meagan; Romero-Kauss, Alba; Hankins, Matthew; Heremans, Annie (Frontiers in Public Health, 2022)
To substantiate the beneficial effects of switching from cigarette smoking to heated tobacco products (HTP), this study conducted a time-trend analysis using data from the Japanese Medical Data Center (JMDC) database. Specifically, we assessed hospitalization numbers for chronic obstructive pulmonary disease (COPD) exacerbations and acute ischemic heart disease (IHD) before and after the introduction of HTPs in the Japanese market. This study replicated a previous study using a different Japanese real-world data source (Medical Data Vision). We retrieved the number of hospitalizations associated with the International Classification of Diseases-10 codes for COPD and IHD from 2010 to 2019—five years before to four years after introducing HTPs in the Japanese market—from the JMDC database. Then, we used interrupted time-series analyses to test the hypothesis that the introduction of HTPs is associated with a reduction in hospitalizations for COPD (all codes), COPD exacerbation, COPD exacerbation plus lower respiratory tract infections (LRTI), and IHD, adjusting for age, sex, seasonality, and flu vaccination rates. Analysis of all available data from the JMDC database revealed a significant reduction in the number of hospitalizations for COPD (all codes; p=0.0001) and IHD using Diagnosis Procedure Combination data on causative disease flags (p<0.00001). We also observed a non-significant reduction in hospitalizations for COPD plus LRTI as well as IHD after HTP introduction in Japan. This study confirmed the findings of our previous study where a decrease in hospitalizations due to COPD exacerbation after the introduction of HTPs in Japan was also shown. Nevertheless, these findings warrant further research to evaluate the impact of HTPs on the health of populations in other countries where these products have been introduced.